Regaining competitiveness putting the goal to work : Updated to include all the changes in the second revised edition of the goal / Mokshagundam L.Srikanth and Harold E. Cavallaro, Jr. 2nd ed - L.Srikanth, Mokshagundam
Gồm: Acknowledgments; Foreword, About the authors...